Surgical Techniques for Myasthenia Gravis: Robotic-Assisted Thoracoscopic Surgery - Li, Feng; Ismail, Mahmoud; Elsner, Aron; Uluk, Deniz; Bauer, Gero; Meisel, Andreas; Rueckert, Jens-C (Thoracic surgery clinics, 2019)
Robotic-assisted thoracoscopic surgery (RATS) creates an extended approach for thymectomy in terms of locating contralateral phrenic nerve and upper poles of the thymus. RATS thymectomy is indicated in all non-thymomatous myasthenia gravis (MG) patients and thymomatous MG patients with resectable thymoma, typically Masaoka-Koga I and II. Left-sided RATS thymectomy is superior for anatomic reasons and in the special care patients with MG. Up to now, left-sided three-trocar RATS thymectomy is the perfect combination of radical resection and minimal invasiveness among various approaches for thymectomy.